Asthma In Adults: Principles Of Diagnosis And Management (The Review of Diabetic Studies, 2025)
Asthma is a chronic respiratory condition that can onset in childhood or adulthood. The chronic nature of the condition can, over a period, lead to decreased lung function, which can cause morbidity and even fatality in some cases. Therefore, it is critical to assess the current diagnostic techniques and treatment modalities to reduce any adversities associated with asthma.Aim: To objectively review the latest methodology for diagnosis and management of asthma in the adult population.Materials and methods: This review is a comprehensive search of PUBMED from the year 2005 to 2025.Conclusion: Asthma is a chronic condition that requires careful and timely diagnosis to prevent lifelong complications and frequent exacerbations. The condition should be conscientiously treated according to the patient’s age, sex, history, and symptoms, along with avoidance of risk factors as much as possible.